Analisis Penerapan Upah Terhadap Tenaga Kerja Dalam Meningkatkan Kinerja Karyawan Menurut Perspektif Syariah (Studi Kasus PT. BPR PNM Syariah Patuh Beramal Bertais Lombok) - Saefurrahman, Ahmad; Addaroni, Muhibban; Amalia, Nurul (Journal of Student Development Information System (JoSDIS), 2024)
Islam is a comprehensive and universal system of life that regulates all aspects, both social, economic and political as well as spiritual life. Islam is comprehensive which means regulating all aspects of human life both in their beliefs, worship, morals and muamalah. One of the very important teachings is the field of muamalah or iqtishadiyah ( Islamic economics).Thus, the government through related institutions is also expected to need to build intense coordination with financial institutions, both institutions financial institutions such as banks and non-bank financial institutions, in an effort to encourage the growth and development of healthy and more independent micro enterprises such as PT. National Capital Madani (PNM).